Малогабаритные цифровые частотомеры сверхвысокочастотного диапазона - Krival, I. I.; Skrypnyuk, A. I.; Protsenko, V. A.; Marjenko, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The article presents the review of operation principles, application, brief technical and metrological characteristics of frequency counters as UA Ч3-63/3, UA Ч3-79M, UA Ч3-101.